INTERDISCIPLINARY INTEGRATION AS A CONDITION FOR THE IMPLEMENTATION OF THE COMPETENCE-BASED APPROACH IN VOCATIONAL EDUCATION - Dranyuk, O.I.; Craft, N.N.; Baeva, T.E.; Krylichevsky, V.I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to experimentally substantiate the pedagogical conditions of interdisciplinary integration in the implementation of the competency-based approach in the educational process of the University of Physical Culture. Methods and structure of the study. Theoretical (analysis and generalization of literature, normative documents, pedagogical experience) and empirical research methods (pedagogical observations, pedagogical and psychological testing, peer review, pedagogical experiment) were used in the scientific work; two Wilcoxon sampling criteria were used to process the experimental data. The pedagogical experiment, in which 30 students participated, was carried out on the basis of the Department of Pedagogy of the Lesgaft National State University of Physical Education, Sports and Health, St. Petersburg in order to test the effectiveness of theoretically based pedagogical conditions for interdisciplinary integration. Results and conclusions. It has been established that the implementation of interdisciplinary links is carried out through all components of the educational process. The logic of designing the interdisciplinary content of an academic discipline is determined. Evaluation funds were developed for the disciplines "Pedagogy", "Pedagogy of physical culture and sports", "Scientific and methodological activity" taking into account the requirements of the professional standards "Coach-teacher", "Coach". Pedagogical conditions of interdisciplinary integration were identified and experimentally substantiated in the course of implementation of the competence-based approach in the educational process of the University of Physical Culture.